Physiotherapy after tibial plateau fracture fixation: A systematic review of the literature - Iliopoulos, Efthymios (SAGE Open Med, 2020)
BACKGROUND: Tibial plateau fractures are frequent injuries that orthopaedic surgeons face. It has been reported that they have a significant negative impact on the patients’ lives, decreasing their quality of live, keeping them of work for long periods of time and reducing their activity levels. AIM: Interestingly, there is not enough focus in the literature about the post-operative rehabilitation of these patients. The aim of the present review is to investigate this field of the literature and try to give answers in four main questions: the range of motion exercises post-surgery, the immobilisation, the weight-bearing status and the ongoing rehabilitation. MATERIALS AND METHODS: A literature search was conducted using the PubMed and the Google Scholar search engines. A total of 39 articles met the criteria to be included in the study. RESULTS: The literature about this subject is scarce and controversial. Early range of motion exercises should be encouraged as soon as possible after the procedure. The immobilisation after plate fixation does not seem to be correlated with any benefits to the patients. The weight-bearing status of the patients was the most controversial in the literature with the early weight-bearing gaining ground at the most recent studies. Tibia plateau fractures can have significant impact on the patients’ lives, so ongoing rehabilitation with focus on quadriceps strengthening and proprioception exercises is recommended. CONCLUSION: The present literature review illuminates the controversy that exists in the literature about the physiotherapy following tibia plateau fracture fixation. Early range of motion exercises and early weight bearing should be encouraged. Immobilisation does not seem to provide any benefit. Ongoing rehabilitation should be considered with the view of better clinical outcomes.